Light-triggered photodynamic nanomedicines for overcoming localized therapeutic efficacy in cancer treatment - choi, ji woong; Sun, In-Cheol; Hwang, Hee Sook; Yoon, Hong Yeol; Kim, Kwang meyung (Elsevier BV, 2022)
Photodynamic nanomedicines have significantly enhanced the therapeutic efficacy of photosensitizers (PSs) by overcoming critical limitations of PSs such as poor water solubility and low tumor accumulation. Furthermore, functional photodynamic nanomedicines have enabled overcoming oxygen depletion during photodynamic therapy (PDT) and tissue light penetration limitation by supplying oxygen or upconverting light in targeted tumor tissues, resulting in providing the potential to overcome biological therapeutic barriers of PDT. Nevertheless, their localized therapeutic effects still remain a huddle for the effective treatment of metastatic- or recurrent tumors. Recently, newly designed photodynamic nanomedicines and their combination chemo- or immune checkpoint inhibitor therapy enable the systemic treatment of various metastatic tumors by eliciting antitumor immune responses via immunogenic cell death (ICD). This review introduces recent advances in photodynamic nanomedicines and their applications, focusing on overcoming current limitations. Finally, the challenges and future perspectives of the clinical translation of photodynamic nanomedicines in cancer PDT are discussed. (C) 2022 Elsevier B.V. All rights reserved.